(untitled) (World Journal of Current Medical and Pharmaceutical Research, 2023)
Type 2 diabetes mellitus is increasingly prevalent in the worldwide and is associated with significant morbidity, mortality, and rising health care costs. Microvascular and, to a lesser extent, macrovascular complications are recognized to result from uncontrolled hyperglycemia. However, intensive therapy to achieve normal glucose levels is not without risk, as demonstrated by increased rates of hypoglycemia, weight gain, and all-cause mortality rates in the intensive treatment arm of the ACCORD trial. In addition, observational studies indicate that the presence of diabetes increases the risk of other comorbidities such as fracture and certain cancers, and treatment choice may affect risk. Thus, in an effort to maintain glucose control, the clinician encounters a complex interplay of primary disease management while simultaneously seeking to avoid complications associated with glucose lowering. The chronic nature of diabetes management, efficacy must be balanced against side effects to achieve a tolerable long-term regimen. The goal of this concept is to identify complications of non-insulin treatment of diabetes. The major classes of medication should be reviewed with special attention given to patient considerations, mechanism of action, effect on weight, and cardiovascular outcomes, and additional class-specific side effects including effects on bone. In addition, effects on β-cell function are rectified. It is possible to identify diabetes mellitus risk years or decades in advance on the basis of numerous personal, historic, and laboratory measures and user-friendly clinical decision-support tool to estimate absolute risk for individuals. The patient families, communities, and health organizations should encourage healthy eating and physical activity and should focus the most intensive diabetes mellitus prevention efforts on those at highest risk for progression to diabetes mellitus.